2009
DOI: 10.2975/32.4.2009.276.284
|View full text |Cite
|
Sign up to set email alerts
|

What do persons with mental illnesses need to quit smoking? Mental health consumer and provider perspectives.

Abstract: These findings are instructive in developing appropriate tobacco cessation services for this population. Specifically, these data have been incorporated into a mental health provider toolkit for smoking cessation and have informed the development of a tobacco cessation intervention study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
72
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 48 publications
(49 reference statements)
0
72
0
4
Order By: Relevance
“…This perception appeared to arise from beliefs that patients would not be interested in quitting smoking 39, 40, 41, 42, that patients would be unable to quit smoking successfully 35, 36, 40 and the view that smoking cessation would be too much for patients to cope with alongside their other issues 36, 39, 41, 42, 43. A minority of studies reported concerns about the negative consequences of quitting smoking, such as concerns about a negative impact on psychiatric symptoms/abstinence 36, 41, the potential effects on medication 36 and a fear that smoking cessation may make patients violent 36.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This perception appeared to arise from beliefs that patients would not be interested in quitting smoking 39, 40, 41, 42, that patients would be unable to quit smoking successfully 35, 36, 40 and the view that smoking cessation would be too much for patients to cope with alongside their other issues 36, 39, 41, 42, 43. A minority of studies reported concerns about the negative consequences of quitting smoking, such as concerns about a negative impact on psychiatric symptoms/abstinence 36, 41, the potential effects on medication 36 and a fear that smoking cessation may make patients violent 36.…”
Section: Resultsmentioning
confidence: 99%
“…A perceived lack of opportunity to provide smoking cessation support was evident 36, 39, 40, 41, 42, 43. This generally arose from a perceived lack of treatment resources either on‐site or to refer patients to off‐site 36, 40, 41, 42 and a lack of guidance for implementing smoking cessation treatment alongside treatment for patients' primary disorders 36, 41, 42, 43.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations